Activating the Monuments - The Ritual Use of Cairns in Bronze Age Norrland - Bolin, Hans (Current Swedish Archaeology, 1998)
This article deals with cairns and stone-settings in Northern Sweden. The central questions are: what was the meaning of the cairns, who built them, and what were the intentions of the people in doing so? Cairns and stonesettings do not only represent a kind of permanent and completed graveconstruction for individual burials. The ritual use of cairns and cairn-like stone-settings also involved a broad spectrum of ritual activities. It is here suggested that the cairns should be related to kinship groups and considered as long-term monuments, which were continually rebuilt and activated in the local ritual.